A Facile Synthesis of Indole Derivatives by a Palladium‐Catalyzed Process Initiated from Ugi Adducts and their Antifungal Activities. Issue 45 (2nd December 2021) - Qiu, Ji‐Ying; Yuan, Ding; Yu, Jing‐Jing; Zhang, Yi; Li, Wen‐Hao; Tang, Zeng‐Xiang; He, Ping; Ren, Zhi‐Lin
Abstract: In this work, an efficient synthesis of indole derivatives through palladium‐catalyzed double isocyanide insertion reactions has been developed. The reaction intermediates could be readily obtained by Ugi reactions. The transformation features broad functional‐group compatibility, commercially available starting materials, and moderate to good reaction yields. Furthermore, the bioactivities of the synthesized compounds were evaluated in mycelial growth tests against Penicilium digitatum and Colletotrichun gloeosporioides, and showed potential antifungal activities. Abstract : Herein, we have disclosed a concise access to the construction of indole derivatives by Pd‐catalyzed double isocyanide insertion reactions initiated from classical Ugi reactions in moderate to good yields. The broad functional‐group compatibility and available starting materials make this method a valuable tool for generating diverse indole derivatives, which are of considerable interest in synthetic and medicinal chemistry. Furthermore, the bioactivities of the synthesized compounds were evaluated against Penicilium digitatum and Colletotrichun gloeosporioides, and showed potential antifungal activities.